Rancangan Sistem Pembangkit Listrik Tenaga Surya (PLTS) Berkapasitas 100 WP dengan Inverter 1000 Watt - Dwi Liestyowati; Iksal Rachman; Eliyana Firmansyah; Mujiburrohman Mujiburrohman (Yayasan Literasi Sains Indonesia, 2022)
Solar energy is a renewable energy source that is abundantly available in Indonesia. One way to utilize solar energy is to convert it into electrical energy using photovoltaic modules or solar panels, which are called solar power plants (PLTS). The construction of PLTS can accelerate the electrification ratio and reduce fossil materials. In this study, the author will design a 100 Wp solar power plant (PLTS) using a 1000watt inverter, while the research uses the Research and Development method, with stages covering system analysis, design, implementation and testing. The manufacture of PLTS is done by identifying components such as solar panels, DC wattmeter, SCC (Solar Charge Controller), battery, 1 Phase MCB, and AC Wattmeter. It can be concluded that to obtain electrical energy, weather conditions greatly affect the working system of solar panels. The maximum voltage from a 100wp solar panel that was designed and tested for 3 days in the worst month conditions was produced on the second and third days with a voltage value of 17.08 Volts at 12:00 noon and a minimum voltage was generated on the second day of testing, namely with a voltage value of 12.00 Volts at 12.00 Volts. 07:00 am. Furthermore, the 100 wp solar panel can only produce a maximum power of 256.01watt which was obtained on the second day of testing with an average voltage and current obtained of 14.19volt and 1.58 Ampere. The condition of the battery takes 5.47 hours or 328 minutes to fully charge energy to 100%. To maximize power gain and get the intensity of sunlight throughout the morning to evening, the use of the Single Axis solar tracker system is very effective.